Efficacy and Durability of Radiopaque Gelified Ethanol in Management of Herniated Discs - Kuhelj, Dimitrij (Radiol Oncol, 2019)
BACKGROUND: Percutaneous image-guided intradiscal injection of gelified ethanol was introduced to treat herniated disc disease lately. The aim of the study was to assess clinical efficacy and durability over a 36 months’ period. PATIENTS AND METHODS: Eighty-three patients (47 males, 36 females, mean age 48.9 years (18–79 years) were treated between May 2014 and December 2015 for 16 cervical and 67 lumbar chronical contained disc herniations. For pain assessment evaluation, the visual analog scale (VAS) was used. Physical activity, the use of analgesics, patients’ satisfaction with the treatment results and patient’s willingness to repeat the treatment were also evaluated. RESULTS: Fifty-nine patients responded to questionnaire. 89.8% had significant reduction in VAS after 1 month (p < 0.001); 76.9% of patients with cervical symptoms and 93.5% of patients with lumbar symptoms. In cervical group it remained stable, while in lumbar group VAS decreased even more during 36 months (p = 0.012). Single patient had spinal surgery. Moderate and severe physical disability prior to treatment (96.6%) was reduced to less than 30% after 12 months. The majority of active patients returned to their regular job (71.1%); 78% needed less analgesics. Only 5.1% patients were not satisfied with the treatment and 10.2% would not repeat the treatment if needed. CONCLUSIONS: Percutaneous image-guided intradiscal injection of gelified ethanol is safe, effective and durable therapy for chronic contained cervical and lumbar herniations. Due to minimal invasiveness and long-lasting benefits, this kind of treatment should be proposed to designated group of patients as first-line therapy.